2021
DOI: 10.3390/foods10123039
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Quantification of 1,2-Propylene Glycol Enantiomers in Baijiu

Abstract: Enantiomers of 1,2-Propylene glycol (1,2-PG) were investigated in 64 commercial Chinese Baijiu including soy sauce aroma-type Baijiu (SSB), strong aroma-type Baijiu (STB), and light aroma-type Baijiu (LTB), via chiral gas chromatography (β-cyclodextrin). The natural enantiomeric distribution and concentration of 1,2-PG in various baijiu were studied to evaluate whether the distribution and content of the two isomers of 1,2-PG were correlated with the aroma type and storage year. The results showed that 1,2-PG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…According to our investigation, the separation of 2-butanol and 2,3-butanediol isomers in wine [ 20 ], and 1,2-propanediol enantiomers in Baijiu [ 6 ] have been successfully separated using hepta-(2,3-di-O-methyl-6-O- tert -butyldimethylsilyl)-β-cyclodextrin (CYCLOSIL-B column) as stationary phase; it is assumed that this stationary phase has a good result on chiral alcohol separation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our investigation, the separation of 2-butanol and 2,3-butanediol isomers in wine [ 20 ], and 1,2-propanediol enantiomers in Baijiu [ 6 ] have been successfully separated using hepta-(2,3-di-O-methyl-6-O- tert -butyldimethylsilyl)-β-cyclodextrin (CYCLOSIL-B column) as stationary phase; it is assumed that this stationary phase has a good result on chiral alcohol separation.…”
Section: Resultsmentioning
confidence: 99%
“…For example, (S) -ethyl lactate has been reported to be a marker of microbial contamination in wine [ 4 ], and the R/S enantiomer ratio of less than 90/10 in 1,2-propanediol in wine could determine wine adulteration [ 5 ]. The enantiomeric ratio of 1,2-propanediol in Baijiu could be used as a potential marker to distinguish the aroma types of Baijiu [ 6 ]. Besides, it has been shown that different enantiomers belonging to the same molecule may have different properties, including odor characteristics, odor thresholds, and even biological activities [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…These can be divided into different categories, including volatile terpenes, volatile phenylpropanoids/benzenoids, and volatile fatty acid derivatives, based on their different metabolic pathways. The most common chiral aroma compounds described in the literature are volatile terpenes, such as dihydro-α-ionone, dihydro-γionone, α-ionone, γ-ionone, linalool, linalool oxide, and α-terpineol [1][2][3][4][5][6][7][8].…”
Section: Chiral Aroma Compounds and Enzymes Producing Chiral Aroma Co...mentioning
confidence: 99%
“…Identification of the exact enzymes and their subcellular locations will be helpful for us to understand their occurrences in plants. (3) Not all plants contain enzymes producing chiral aroma compounds. Why do some enzymes producing chiral aroma compounds occur in many plants and some others are only present in certain plants?…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…Studies on the differentiation of different aroma types of Baijiu and their authenticity usually involve sensory evaluation, as well as some characteristic chemical compounds. There are certain differences in the content and flavor of certain characteristic chiral flavor substances in different aromatic Baijiu, such as the 1,2-propanediol isomers in Baijiu that we studied previously, where the S-configuration was dominant in SSB, the R-enantiomer was dominant in STB, while neither S- nor R-enantiomer were detected in LTB [ 6 ].…”
Section: Introductionmentioning
confidence: 99%